1984
DOI: 10.1111/j.1528-1157.1984.tb03452.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Persistence of Kindled Seizures After Repeated Injections of Pentylenetetrazol in Rats and Guinea Pigs

Abstract: Pentylenetetrazol (PTZ) was injected into rats (30 or 35 mg/kg) and guinea pigs (40 or 45 mg/kg) daily or every second day. A progressive development of seizure activity after this treatment was observed. Doses ineffective after the first injection induced tonic seizures after 20 injections. Both kinds of treated animals immediately developed tonic seizures when PTZ was injected after a few months interruption for one time only. The results support the assumption that seizures induced by chronic injection of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 16 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…The repeated injections of such a subconvulsant dose during the five experiments should have produced a progressive sensitization to the effects of PTZ in the animals, which became kindled (46). It has been shown that doses ineffective after the first injection induce tonic seizures after 20 injections (47) and that kindling effect is proportional to the dose of PTZ (48). The decrease of crisis latency and the increase of clonus duration among the control experiments show that kindling increased sensitivity to PTZ convulsant effects.…”
Section: Discussionmentioning
confidence: 91%
“…The repeated injections of such a subconvulsant dose during the five experiments should have produced a progressive sensitization to the effects of PTZ in the animals, which became kindled (46). It has been shown that doses ineffective after the first injection induce tonic seizures after 20 injections (47) and that kindling effect is proportional to the dose of PTZ (48). The decrease of crisis latency and the increase of clonus duration among the control experiments show that kindling increased sensitivity to PTZ convulsant effects.…”
Section: Discussionmentioning
confidence: 91%
“…Calibration scale is 1 mm for all panels. Epilepsia ILAE epilepsy/seizure features in these models were cursorily described (Diehl et al, 1984;Popova et al, 2008). Our method induced acute nonconvulsive SE with a very high efficiency, since in only two animals KA injection failed to be effective.…”
Section: Discussionmentioning
confidence: 96%
“…Our study demonstrates that neuropathologic and electroclinical features representative of human mTLE can be reproduced in the guinea pig after local, unilateral injection of KA in one dorsal hippocampus. Attempts to develop a chronic epilepsy model in this animal species were few and epilepsy/seizure features in these models were cursorily described (Diehl et al., 1984; Popova et al., 2008). Our method induced acute nonconvulsive SE with a very high efficiency, since in only two animals KA injection failed to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures were induced in IRs and ARs individually with lithium (3 mEq/kg) followed by pilocarpine injected intraperitoneally (40 mg/kg) 18-20 h later. According to Smialowski's six category classification of seizures [11], rats with IV or V class seizures of 1-h duration were admitted. Fifteen minutes after the onset of the seizure, rats were injected intraperitoneally with atropine (1 mg/kg, He Feng Tragacanth Company, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%